The predictive validity of a Brain Care Score for late-life depression and a composite outcome of dementia, stroke, and late-life depression: data from the UK Biobank cohort - Singh, Sanjula D.; Rivier, Cyprien A.; Papier, Keren; Chemali, Zeina; Gutierrez-Martinez, Leidys; Parodi, Livia; Mayerhofer, Ernst; Senff, Jasper; Clocchiatti-Tuozzo, Santiago; Nunley, Courtney; Newhouse, Amy; Ouyang, An; et al. (Frontiers in Psychiatry, 2024)
The 21-point Brain Care Score (BCS) is a novel tool designed to motivate individuals and care providers to take action to reduce the risk of stroke and dementia by motivating lifestyle changes. Because late-life depression is increasingly recognized to share risk factors with stroke and dementia, and is an important clinical endpoint for brain health, we tested the hypothesis that a higher BCS is associated with a reduced incidence of future depression as well as with a brain health composite outcome comprising stroke, dementia and late-life depression. The BCS was derived from the United Kingdom Biobank baseline evaluation in participants with complete data on BCS items. Associations of BCS and risk of subsequent incident late-life depression and composite brain health outcome were estimated using multivariable Cox proportional hazard models, adjusted for age at baseline and sex assigned at birth. A total of 363,323 participants were included in this analysis with a median BCS at baseline of 12 (IQR: 11-14). There were 6,628 incident cases of late-life depression during a median follow-up period of 13 years. Each five-point increase in baseline BCS was associated with a 33% lower risk of incident late-life depression (95%CI: 29%-36%) and a 27% lower risk of incident composite outcome (95%CI: 24%-30%). These data further demonstrate the shared risk factors across depression, dementia and stroke. Additional validation of the BCS is warranted on the weighing of its components, motivational aspects, and acceptability and adaptability in routine clinical care worldwide. C.D.A.